2019
DOI: 10.1002/anie.201909477
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Electron Localization of Gold Enables the Control of Nitrogen‐to‐Ammonia Fixation

Abstract: The (photo)electrochemical N2 reduction reaction (NRR) provides a favorable avenue for the production of NH3 using renewable energy in mild operating conditions. Understanding and building an efficient catalyst with high NH3 selectivity represents an area of intense interest for the early stages of development for NRR. Herein, we introduce a CoOx layer to tune the local electronic structure of Au nanoparticles with positive valence sites for boosting conversion of N2 to NH3. The catalysts, possessing high aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
81
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(85 citation statements)
references
References 31 publications
4
81
0
Order By: Relevance
“…Recently, many noble metals are used as efficient electrocatalysts for NRR. [ 1,15‐20 ] However, the very high cost of noble metals limits their commercialization in industry. The earth‐abundant NRR catalysts such as the iron oxides nanoparticles are extensively investigated for NRR due to their low‐cost, distinct electronic properties, and separation easiness.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many noble metals are used as efficient electrocatalysts for NRR. [ 1,15‐20 ] However, the very high cost of noble metals limits their commercialization in industry. The earth‐abundant NRR catalysts such as the iron oxides nanoparticles are extensively investigated for NRR due to their low‐cost, distinct electronic properties, and separation easiness.…”
Section: Introductionmentioning
confidence: 99%
“…(Figure 6b). [67] Fang et al [23] used Mxenes materials as a nucleation site to generate relatively stable TiO 2 . In this way, a heterojunction structure of TiO 2 NPs distributed on the 2D Ti 3 C 2 T x nanosheets (TiO 2 /Ti 3 C 2 T x , "T" is the terminal groups of F) could be easily formed.…”
Section: Interface Between Metal (Compound) and Metal Compoundmentioning
confidence: 99%
“…It has been proposed that the surface oxidation state (M d+ ) active sites in metallic catalysts play a crucial role in the electrocatalytic process and can cause the redistribution of the surface electronic structure, thereby enhancing the absorption of radical species and reactants. [67] Zheng et al [67] used a CoO x layer to adjust the local electronic structure of Au nanoparticles with positive valence sites to promote the conversion of N 2 to NH 3 . Catalysts of this type, which possess high average oxidation states (≈40%), achieve a good NH 3 yield rate of 15.1 µg cm −2 h −1 and a good Faraday efficiency of 19% at −0.5 V versus RHE.…”
Section: Interface Between Metal (Compound) and Metal Compoundmentioning
confidence: 99%
“…This is the area where most of the recent research on N 2 fixation (often indicated as N 2 reduction reaction, NRR) is focused, with the direct photocatalytic reduction of N 2 . A selection of recent reviews on these aspects are presented in [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%